The Influence Of E-Service Quality And Price Discount On Purchasing Decisions In TikTok Shop In Bogor - Martiwi, Rini; Suharyadi, Dedi; Nuryati, Siti; Aryadi, Heri (SEAN Institute, 2024)
This research examines the influence of e-service quality and price discounts on the purchasing decisions of TikTok Shop customers in Bogor. This research uses a quantitative descriptive method by distributing questionnaires via Google Form with purposive sampling, namely Tiktok Shop users as an online shopping platform for consumers in Bogor. The sample was taken using a purposive sampling method of 180 respondents. In analyzing the research data, SPSS 26 was used to calculate the results of the Multiple Linear Regression variable test, t-test, F test, and determination analysis. Based on the t-test, this research shows that e-service quality and price discounts positively affect Tiktok Shop customers' purchasing decisions. Based on the results of the F Test, e-service quality and price discounts significantly influence purchasing decisions at the TikTok Shop in Bogor. Based on the results of multiple regression analysis, the effect of e-service quality and price discount on purchasing decisions at the TikTok Shop in Bogor is only 51.7%. In comparison, the remaining 48.3% is influenced by other variables not examined in this research.